International Master's Degree Students' Well-being at a Finnish University During COVID-19 - Pappa Sotiria; Yada Takumi; Perälä-Littunen Satu (De Gruyter, 2020)
The rapid developments and consequences of the COVID-19 crisis for university students' well-being are presently being studied across the world. This study contributes to the growing discourse on university students' well-being by exploring changes in international Master's degree students' well-being in relation to the move to online teaching and learning at a Finnish university during the COVID-19 pandemic. The study draws on 37 answers to an open-ended question about remote teaching and learning at the end of a survey on university students' stress. The text data were analysed conducting a preliminary quantitative content analysis and a more detailed thematic analysis, from which two themes were developed. The first theme concerned respondents' well-being with regard to their friends and family, including the desire for human connection, ways of coping and health concerns. The second theme concerned respondents' well-being with regard to their studies, including the importance of social life on campus, affected concentration and motivation, degree-related complications, and online teaching and supervision. The findings suggest that sociocultural well-being may extend beyond acculturation and that decreased psychological well-being has repercussions for international students' studies. The study concludes with a discussion of the study's limitations and practical implications.